TRANSFORMASI CHANNEL SYSTEM KE LABELLED TRANSITION SYSTEM - Siti Mutmainah; Reza Pulungan (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2012)
A parallel system must be developed with extra precision to achieve a high level of dependability to produce error-free software. Therefore, we need an appropriate and formal model of the system. The model is necessary for verification software in model checking. A model that is often used in model checking is Labelled Transition System (LTS). An LTS can be generated from Program Graphs (PG), which are representations of programs in any programming language. However, in modeling a parallel system we need to describe the communications(model of interactivity) between the Program Graphs. For this purpose, we need and use Channel Systems (CS). Therefore, we often need to transform CS to LTS. The aim of this research is to developa transformation algorithm to generate an LTS from a given CS. Through the concept of parallelism, the algorithm is constructed by exploiting the so-called Structured Operational Semantic (SOS) of the CS. The transformation algorithm is implemented by developing a prototype tool designed with 3 essential components:input, process and output. Input is a text file that contains a model of a parallel system in the form of a CS. The model will be processed by using thetransformation algorithm that generates an LTS as output text file. Functionally, the algorithm can handle models of parallel systems written ina CS that consists of several PGs containing both looping and branching. Moreover, it has ability to satisfy various parallelism models such as interleaving, synchronous and asynchronous.